lncRNAs Regulate Innate Immune Responses and Their Roles in Macrophage Polarization - Zhen Wang; Ying Zheng (Mediators of Inflammation)
The innate immune system is the first line of defense against microbial pathogens. The activated innate immune system plays important roles in eliciting antimicrobial defenses. Despite the benefits of innate immune responses, excessive inflammation will cause host damage. Thus, tight regulation of these processes is required for the maintenance of immune homeostasis. Recently, a new class of long noncoding RNAs (lncRNAs) has emerged as important regulators in many physiological and pathological processes. Dysregulated lncRNAs have been found to be associated with excessive or uncontrolled inflammation. In this brief review, we summarize the roles of functional lncRNAs in regulating innate immune responses. We also discuss the roles of lncRNAs in macrophage polarization, an important molecular event in the innate immune responses.